Minocycline suppresses disease-associated microglia (DAM) in a model of photoreceptor cell degeneration. (April 2022) - Ozaki, Ema; Delaney, Conor; Campbell, Matthew; Doyle, Sarah L.
Abstract: As the resident immune cells in the retina, microglia play important homeostatic roles in retinal immune regulation and neuroprotection. However, chronic microglia activation is a common hallmark of many degenerative retinal diseases. The semi-synthetic tetracycline antibiotic, minocycline, appears to inhibit pro-inflammatory microglia which coincides with protection against photoreceptor cell degeneration. A sub-type of microglia termed disease associated microglia ( DAM) have recently been associated with a wide range of central nervous system (CNS) diseases. In this study we examine the kinetics of microglia infiltration towards the outer retina of rhodopsin knockout mice ( Rho −/− ) by immunofluorescence, and undertake transcriptional and spatial localization analysis of markers for evidence of both homeostatic function and appearance of DAM. We demonstrate in the Rho −/− mice, IBA1 + and P2RY12 + microglia take on an activated morphology early in disease, prior to notable photoreceptor loss and are capable of infiltrating the subretinal space. Expression of lipid processing enzyme and DAM-marker lipoprotein lipase (LPL) is primarily observed only after microglia have traversed the ONL. Administration of minocycline to Rho −/− mice induced loss of phagocytic/DAM microglia in the outer retina in vivo coinciding with photoreceptor survival and amelioration of retinal degeneration. Overall, we show that minocycline suppresses many DAM markers, in particular those associated with lipid metabolism indicating that suppression of this process is one mechanism by which minocycline protects against inflammation induced photoreceptor cell death. Highlights: Microglia infiltrating the subretinal space in the rhodopsin knockout ( Rho−/−) model of retinal degeneration display DAM markers. Administration of semi-synthetic broad spectrum tetracycline antibiotic minocycline to Rho−/− mice significantly reduces DAM-markers in the outer retina. We identify microglial lipid processing enzyme LPL as a target of minocycline A reduction in LPL coincides with protection of photoreceptors when Rho−/− mice are administered minocycline as a treatment